Eye movement desensitization and reprocessing: A conceptual framework - Menon Sukanya; Jayan C (Indian Journal of Psychological Medicine, 2010)
Eye movement desensitization and reprocessing (EMDR) is a method which was initially used for the treatment of post-traumatic stress disorder. But it is now being used in different therapeutic situations. EMDR is an eight-phase treatment method. History taking, client preparation, assessment, desensitization, installation, body scan, closure and reevaluation of treatment effect are the eight phases of this treatment which are briefly described. A case report is also depicted which indicates the efficacy of EMDR. The areas where EMDR is used and the possible ways through which it is working are also described.